The Implementation Lestari School of Malaysia Using Three Pillars of Sustainability Model Dimension - Izzati Zulkifli, Siti; AP. , Zainudin Hassan (International Journal of Psychosocial Rehabilitation, 2020)
The various programs related to sustainable school programs have been organized by the government and private sectors in Malaysia, but little research on the programs is being done. In The three pillars of sustainability, namely economic, environmental, and social pillars, are widely used when discussing sustainability, as sustainable development can only be achieved when all three pillars of sustainability are equally represented. It is important to include the three pillars of sustainability when developing a program related to sustainability to be internationally recognized and measurable against the international standard. This paper identifies the presence of three sustainability pillars, namely the economic, social, and environmental development of sustainable school programs and existing models. This paper is carried out qualitatively, using semi-structured interviews with teachers actively involved in sustainable school programs. The finding shows that sustainable school programs in Malaysia have three pillars of sustainability, though not equally represented. Based on data analysis using NVivo software, the comparison made is based on the reference and coverage of the three pillars of sustainability dimension. It achieves the highest economic dimension in terms of reference and coverage, while the lowest is the social dimension based on school performance. It could be expected that the Lestari school is mostly concerned with the economic side of sustainability. This study suggests improvement of sustainable school programs in Malaysia is necessary in order for the three pillars of sustainability to be equally represented.